2021
DOI: 10.3892/etm.2021.9991
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA ADAMTS9‑AS2 inhibits liver cancer cell proliferation, migration and invasion

Abstract: Long non-coding RNA (lncRNA) ADAM metallopeptidase with thrombospondin type 1 motif 9 antisense RNA 2 (ADAMTS9-AS2) is involved in various types of cancer, such as ovarian cancer, lung cancer and clear cell renal cell carcinoma. However, the roles of ADAMTS9-AS2 in liver cancer are not completely understood. The present study aimed to determine the functional role of ADAMTS9-AS2 in human liver cancer and investigate the potential underlying molecular mechanisms. The expression levels of ADAMTS9-AS2 and ADAMTS9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…31 ADAMTS9-AS2 inhibited PI3K/AKT/mTOR signaling pathway and thereby suppressed the proliferation, migration, and invasion of hepatocellular carcinoma cells. 32 In this study, based on GESA, ADAMTS9-AS2 was related to pathways including unwinding of DNA, extrinsic pathway, polo-like kinasemediated events, cori cycle, MCM pathway, proteasome pathway, lagging strand synthesis, PCNA-dependent long patch base excision repair and regulation of gene expression in beta cells.…”
Section: Discussionmentioning
confidence: 94%
“…31 ADAMTS9-AS2 inhibited PI3K/AKT/mTOR signaling pathway and thereby suppressed the proliferation, migration, and invasion of hepatocellular carcinoma cells. 32 In this study, based on GESA, ADAMTS9-AS2 was related to pathways including unwinding of DNA, extrinsic pathway, polo-like kinasemediated events, cori cycle, MCM pathway, proteasome pathway, lagging strand synthesis, PCNA-dependent long patch base excision repair and regulation of gene expression in beta cells.…”
Section: Discussionmentioning
confidence: 94%
“…For example, ADAMTS9-AS2 is considered as a tumor suppressor in inhibiting the migration of glioma cells, with the regulation by DNMT1 ( 53 ). ADAMTS9-AS2 upregulation also suppresses cancer cell progression in lung cancer ( 54 ), liver cancer ( 55 ), and gastric cancer ( 56 ). LINC00968 serves as oncogenic or tumor-suppressive roles in different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several lincRNAs are signi cantly correlated with cancer diagnosis, prognosis, and the therapeutic development of multitype cancers [54][55][56] . Our data indicated that several lincRNAs could function as potential prognostic biomarkers and have important clinical value, e.g., RFPL1S, ADAMTS9-AS2, IBA57-AS1, and MYOSLID are up-regulated lincRNAs [57][58][59][60][61][62] and MORF4L2-AS1, LINC01278, and LINC00562 63-67 are down-regulated. Importantly, all are related to the occurrence and development of several tumors by modulating "PI3K-Akt signaling", "interferon type II signaling" and the expression of particular genes.…”
Section: Discussionmentioning
confidence: 99%